Dynamics and trends of drug dealing: A local labour system perspective - Manuela Pulina; Alessandro Salis (Masaryk University, Faculty of Economics and Administration, 2024)
This study provides a dynamic analysis of illegal drug trafficking in the Italian region of Sardinia, using the Local Labour Systems (LLS, ISTAT) framework. Data from major regional newspapers (January 2017 - De-cember 2022) were validated through institutional reports. A multivariate biplot analysis reveals an increase in drug seizures and the Island's role as a hub for national and international drug trade, facilitated by local and traditional mafia organizations. Related crimes are also infiltrating the le-gal economy, particularly in the coastal real estate market. This study high-lights the urgent need for targeted institutional and community strategies to protect younger people, who are increasingly involved in trafficking.
Keywords: K42; O17; R12; C38; 330; Drugtrafficking; Organized Crime; Local Labour Systems; Multivariate Biplot